2011
DOI: 10.1016/s1413-8670(11)70157-x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis and human papillomavirus coinfection: association with p16INK4a and Ki67 expression in biopsies of patients with pre-neoplastic and neoplastic lesions

Abstract: The objective of this study was to identify the frequency of coinfection by human papillomavirus (HPV) and Chlamydia trachomatis (CT) in cervical lesions and relate it with immunohistochemical expression of p16INK4a and Ki67, both oncogenicity markers. A cross-sectional study with 86 women from primary care units in southern Brazil was conducted. Cervical swabs were collected for HPV-DNA and CT-DNA detection, through the polymerase chain reaction technique (PCR). The immunohistochemical analysis was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Other similar studies have shown that Ct infection was not associated with CC, because the prevalence of bacteria is very low in this cancer. 10,11 However, a positive or negative association between HPV, Ct, and CC has been found in studies comparing results obtained by different methodologies, such as serological status for Ct and HPV, presence of one or another agent by highly sensitive molecular techniques, and others by serological status. [10][11][12] Because of these methodological differences, it is difficult to compare results from different studies, and caution is needed in interpreting the possible existence of any linkage between Ct and cervical carcinogenesis.…”
mentioning
confidence: 99%
“…Other similar studies have shown that Ct infection was not associated with CC, because the prevalence of bacteria is very low in this cancer. 10,11 However, a positive or negative association between HPV, Ct, and CC has been found in studies comparing results obtained by different methodologies, such as serological status for Ct and HPV, presence of one or another agent by highly sensitive molecular techniques, and others by serological status. [10][11][12] Because of these methodological differences, it is difficult to compare results from different studies, and caution is needed in interpreting the possible existence of any linkage between Ct and cervical carcinogenesis.…”
mentioning
confidence: 99%
“…Furthermore, links with other markers of increasing malignancy like p16INK4a (Calil et al, 2011) and effects on host DNA damage and proliferation as well as DNA damage responses (Chumduri et al, 2013) could not be addressed in the present work. Future studies should take these possibilities into consideration to allow a more comprehensive picture of the influence of C. trachomatis infection on cervical cancer development in Thailand to be obtained.…”
Section: Discussionmentioning
confidence: 95%
“…Hipotetiza-se que a CT também predispõe a gravidez ectópica por alteração da expressão FTPROKR, e que é maior em mulher com infecção passada por CT 19 . Outros fatores de risco são identificados pelos autores, tais como, flora vaginal anormal 21 , presença de condiloma acuminado, inflamação discreta, instrumentação do útero, tipo de atividade facilitadora (por exemplo, entre profissionais do sexo), consumo de álcool, uso de algodão ou absorvente, uso de substâncias ou produtos de higiene vaginal para o sexo [22][23] . Dentre os 174 artigos selecionados para a revisão, 56 mencionaram a prevalência obtida.…”
Section: Discussionunclassified